Analysis of Antioxidant Capacity Variation among Thai Holy Basil Cultivars (Ocimum tenuiflorum L.) Using Density-Based Clustering Algorithm - Tanapon Saelao; Panita Chutimanukul; Apichat Suratanee; Kitiporn Plaimas (Horticulturae, 2023)
Holy basil (Ocimum tenuiflorum L.) is a widely renowned herb for its abundance of bioactive compounds and medicinal applications. Nevertheless, there exists a dearth of knowledge regarding the variability among holy basil cultivars capable of yielding substantial bioactive compounds. This study aims to address this gap by shedding light on the diversity of antioxidant capacities within different accessions of Thai holy basil by employing a density-based clustering algorithm to categorize the holy basil cultivars that demonstrate notable antioxidant potential. The study involves the analysis of the anthocyanin, flavonoid, phenolic, and terpenoid content, as well as DPPH antioxidant activity, in 26 Thai holy basil accessions collected from diverse locations in Thailand. Among the 26 tested Thai holy basil cultivars, terpenoids were found to be the dominant class of compounds, with average values of 707 mg/gDW, while the levels of flavonoids and phenolic compounds remained below 65 mg rutin/gDW and 46 mg GAE/gDW, respectively. The DPPH assay in holy basil cultivars demonstrated that the antioxidant activity ranged between 50% and 93%. After standardizing the data, the clustering results revealed four distinct groups of cultivars: the first group, with low antioxidant levels; the second group, with high terpenoid content; the third group, with high flavonoid, DPPH antioxidant activity, and phenolic content; and the fourth group, with elevated levels of anthocyanin, DPPH antioxidant activity, and phenolic content. A strong positive correlation was observed among DPPH antioxidant activity, flavonoids, and phenolics. Specific cultivars: The Red, OC108, and OC106 holy basil cultivars in cluster 4 exhibited high anthocyanin and phenolic production. In cluster 3, the accessions OC113, OC057, OC063, and OC059 showed high DPPH antioxidant activity, flavonoids, and phenolics, while, in cluster 2, only accessions from Udon Thani, Thailand—namely OC194 and OC195—displayed high terpenoid content. Ultimately, this study significantly contributes to the inherent diversity in the antioxidant capacities among various Thai holy basil cultivars. It lays the foundation for targeted breeding strategies and informed choices regarding consumption. The comprehensive insights from this analysis hold the potential to accurately identify holy basil cultivars with promising applications in medicine, functional foods, and the nutraceutical industry.